Schmerzengeld für Schock- und Trauerschäden Rechtsvergleichende Analyse des Angehörigenbegriffes und der Mitverschuldensanrechnung - Stiegler, Anita Maria (2009)
The doctoral thesis is a comparing study of the Austrian, German, Swiss, England and French tort law, also contains the Principles of the European Group of tort law and handle four major questions: (1) Who are the close relatives? (2) What is the difference between close relatives and other people who suffer a damage because of the harm of another person? (3) Is it possible that the tortfeasor hold the fault of the victime against the close relatives who suffer nervous shock or bereavement? (4) Do the close relatives have a right to claim for damage on their own or is that related to the claim of the victime?